2007
DOI: 10.1073/pnas.0703854104
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor juxtamembrane region regulates allosteric tyrosine kinase activation

Abstract: Structural studies of the extracellular and tyrosine kinase domains of the epidermal growth factor receptor (ErbB-1) provide considerable insight into facets of the receptor activation mechanism, but the contributions of other regions of ErbB-1 have not been ascertained. This study demonstrates that the intracellular juxtamembrane (JM) region plays a vital role in the kinase activation mechanism. In the experiments described herein, the entire ErbB-1 intracellular domain (ICD) has been expressed in mammalian c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
137
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(146 citation statements)
references
References 32 publications
9
137
0
Order By: Relevance
“…Thus, it is likely that both CaM species may bind to this site in living cells. The identification of P-(Tyr)-CaM as a potential intracellular ligand of the EGFR introduces further complexity to the proposed activation mechanism of this receptor [9,[29][30][31]. Thus, we suggest the existence of three fundamental states of the EGFR tyrosine kinase: (i) an inactive state in the absence of EGF in which the CaM-BD is electrostatically bound to the inner leaflet of the plasma membrane as first proposed by McLaughlin et al [25]; (ii) a partially-active state of the receptor in the presence of EGF when apo-CaM is phosphorylated and P-(Tyr)-CaM detaches the tyrosine kinase domain from the membrane; and (iii) a fully-active state in the presence of EGF when Ca 2 + /P-(Tyr)-CaM plus non-phosphorylated Ca 2 + -CaM are present, as the former plays a more efficient activating role and the latter may also accumulate after Ca 2 + /P-(Tyr)-CaM dephosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is likely that both CaM species may bind to this site in living cells. The identification of P-(Tyr)-CaM as a potential intracellular ligand of the EGFR introduces further complexity to the proposed activation mechanism of this receptor [9,[29][30][31]. Thus, we suggest the existence of three fundamental states of the EGFR tyrosine kinase: (i) an inactive state in the absence of EGF in which the CaM-BD is electrostatically bound to the inner leaflet of the plasma membrane as first proposed by McLaughlin et al [25]; (ii) a partially-active state of the receptor in the presence of EGF when apo-CaM is phosphorylated and P-(Tyr)-CaM detaches the tyrosine kinase domain from the membrane; and (iii) a fully-active state in the presence of EGF when Ca 2 + /P-(Tyr)-CaM plus non-phosphorylated Ca 2 + -CaM are present, as the former plays a more efficient activating role and the latter may also accumulate after Ca 2 + /P-(Tyr)-CaM dephosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…[ [29][30][31], giving further credibility to the presumptive implication of CaM in the EGFR activation process. Although Ca 2 + -CaM is involved in ligand-dependent EGFR activation [21][22][23]25], it is not clear whether or not phospho-(Tyr)-CaM (tyrosinephosphorylated CaM) also plays an activating role in this process.…”
Section: Introductionmentioning
confidence: 99%
“…Amino acids in this region have been shown to serve as binding and phosphorylation sites for signaling molecules. [45][46][47][48][49][50] The importance of the JM domain in signaling is evident from several mutations, deletions and insertions in this domain that can lead to cancer. [51][52][53] In addition, recent studies have provided evidence for the active role of the JM domains in regulating RTK activity.…”
Section: Juxtamembrane Domainsmentioning
confidence: 99%
“…On the contrary, the JM domain has been shown to be essential in the activation of the kinase. 50 Recent studies have suggested that the role of the JM domain is to stabilize the activated asymmetric kinase dimer by forming an antiparallel dimer with the JM segment of the other receptor. 58,59 Furthermore, quantitative studies of ligand binding as a function of receptor expression have shown that the binding affinity of the ligand to the extracellular domain is affected by the JM domain.…”
Section: Juxtamembrane Domainsmentioning
confidence: 99%
“…This again suggests that the proposed anti-parallel helical dimer contributes to the negative cooperativity. It has long been recognized that phosphorylation of EGFR T678 (T654 in mature EGFR) leads to decreased affinity of EGF and loss of EGF-stimulated receptor autophosphorylation [78][79][80][81][82]. Phorbol 12-myristate 13-acetate-induced phosphorylation of T678 by protein kinase C leads to the complete loss of cooperativity [77].…”
Section: Negative Cooperativity In Ligand Binding To Egfrmentioning
confidence: 99%